Embedding Multicultural Values in Islamic Education: A Portrayal of Contemporary Indonesian Textbooks - Muhammad Aji Nugroho (Edukasia Islamika, 2019)
The incorporation of multicultural values ​​in Islamic education textbooks needs to be fostered as the endeavor to raise Muslim’s inclusive religious awareness. In response to this growing need, this study describes the highlight of multicultural education and multicultural values-based learning materials of Islamic education as well as well-planned learning processes. Grounded in a qualitative explorative descriptive study, it provides a comprehensive content analysis of Islamic education textbooks reinforced with a phenomenological approach. The primary sources of research were Islamic education textbooks for tenth, eleventh, and twelfth grades in secondary high schools located in Salatiga, Central Java, Indonesia. Secondary sources were obtained through in-depth interviews with the teachers and students. Findings of this study demonstrate that firstly, not only did the textbooks cover the transfer of knowledge, but they also promoted multicultural values, so that the students upheld their cultural identities. Secondly, the learning materials introduced not only ritualistic symbols, but also the relationship between religious symbols and the existing reality. It encourages the students to think inclusively regarding unity in diversity. Finally, multicultural values embedded in the learning process involved tolerance, harmony, a culture of mutual respect, democracy, and maintenance of faith with good morality in social solidarity and interaction.